2021
DOI: 10.1007/s10886-021-01246-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics Reveal the Survival Strategies of Enterococcus mundtii in the Gut of Spodoptera littoralis

Abstract: The complex interaction between a higher organism and its resident gut flora is a subject of immense interest in the field of symbiosis. Many insects harbor a complex community of microorganisms in their gut. Larvae of Spodoptera littoralis, a lepidopteran pest which is prevalent in tropical and subtropical regions of the world, have a tube-like gut structure containing a simple bacterial community. This community varies both spatially (along the length of the gut) and temporally (during the life cycle of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 85 publications
0
17
0
Order By: Relevance
“…The gut microbial communities of lepidopterans should be similar to the microbiota of the food ingested. But other investigations showed lepidopterans hosted a core microbial community in their guts, which was distinctive from that obtained from the food source ( Mason et al, 2020 ; Mazumdar et al, 2021 ). The importance of microorganisms in larval lepidopterans is presently debatable.…”
Section: Introductionmentioning
confidence: 78%
“…The gut microbial communities of lepidopterans should be similar to the microbiota of the food ingested. But other investigations showed lepidopterans hosted a core microbial community in their guts, which was distinctive from that obtained from the food source ( Mason et al, 2020 ; Mazumdar et al, 2021 ). The importance of microorganisms in larval lepidopterans is presently debatable.…”
Section: Introductionmentioning
confidence: 78%
“…E. casseliflavus can support house fly larval development and colonize the gut of teneral adults to various degrees ( Anuradha et al., 2014 ). E. mundtii with adherence properties can form a biofilm layer on the gut wall to help insect adapt to altered environments ( Mazumdar et al., 2021b ). Probiotic characterization of E. mundtii was observed from larval gut of Plutella xylostella ( Mazumdar et al., 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…The other scenario that our results put forward is that specific members of Enterococcus could have an impact in reducing larval growth rate. Enterococci are lactic acid bacteria well adapted to survival in the harsh gut environment by evading host defences (Fiore et al 2019, Mazumdar et al 2021) and commonly found in Lepidoptera throughout their life cycle (Hammer et al 2014, Chen et al 2016, Teh et al 2016, González-Serrano et al 2020). The specific enterococci we detected in connection to slower growth clustered with E. casseliflavus and E. gallinarum , which can be the dominant bacteria in Lepidoptera (Martin & Mundt 1972, Tang et al 2012, Shao et al 2014, Jones et al 2019).…”
Section: Discussionmentioning
confidence: 99%